Evaluation of cardio protective Phytochemicals from Phyllanthus maderaspatensis- an in vitro, in vivo and in silico approach (Advances in Applied Biological Research, 2025)
Background: Plants are used as complementary and alternative medicine for a  variety of conditions, regardless of their crude or as their separated pharmacological  components. The purpose of this study was to assess in vitro antioxidant and  in vivo cardio protective of the Phyllanthus maderaspatensis. Methodology:  Quantitative analysis and Gas Chromatography-Mass Spectrometry (GC-MS)  phytochemical study based on solvent method of extraction were carried out.  Using the conventional method of antioxidant assay among the leaf extract were  ascertained. Isoproterenol (ISO)-treated rats were used for in vivo experiment to  check the effect of plant extract on cardio protective bio markers. Results. There is  an increased total antioxidant activity of extract found in a dose-dependent manner.  At 50 μg, 19-24% activity and at 400 μg, 79-84% scavenging potential was recorded.  The rats receiving the extract showed a decrease in heart weight and an increase in  body weight. The mean concentration of cardiac troponin (cTn) T/I in the serum  of rats treated with the standard drug reduced effectively (1.13±0.07/0.64±0.05  ng/mL), whereas significantly by the extract (1.25±0.19/0.72±0.08 ng/mL). The  creatine kinase MB (CKMB) of the standard was significant at 78.33±6.26IU, and  the extract was 83.35±7.51IU. The data showed increased values among the standard  and extract compared to the control group but were found to be significantly (p
Keywords: Cardiac Troponin; Creatine Kinase; Cardioprotection; Biomarkers; Medicinal Plant